Ear shut and Dentistry: ethical and legal approach - Paulo Henrique Viana Pinto; Juliane Bustamante Sá dos Santos; Antônio Castelo-Branco; Cindy maki Sato; Marconi Delmiro Neves da Silva; Ricardo Henrique Alves da Silva (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: As a health science, dentistry seeks to raise self-esteem and improve patients’ quality of life. However, the emergence of the aesthetic procedure “ear shut,” which proposes correcting protruding ears without surgery, has raised ethical and legal doubts in the dental profession, especially concerning the limits of professional activity. Objective: To conduct a survey of the laws, norms, and resolutions on the area of performance of dental surgeons, as well as to discuss the limits and consequences of their extrapolation from the perspective of the procedure propagated as “ear shut.” Method: A search was carried out for administrative norms on the Federal Council of Dentistry (CFO) websites and the Federal Council of Medicine and legal provisions on the Portal da Legislação website. Results: In the civil sphere, the disclosure of procedures such as the “ear shut” can characterize a promise of result and lead to judicial accountability. Exceeding professional boundaries constitutes an illegal exercise and a crime under the Brazilian Penal Code. In addition to not covering the area of clinical practice of dentists, at the administrative level, CFO Resolutions No. 198/2019 and No. 230/2020 emphasize that ear procedures are not part of the scope of procedures relevant to Dentistry and may lead to ethical infractions and consequent administrative proceedings. Conclusion: At present, based on the skills, prohibitions, rights, and duties of dentists, it can be stated that performing the “ear shut” by these professionals confronts civil, criminal, and administrative obligations.